Analysis of The Cost Comparison of Bridge Floor Plate Formr on Toll Road Project - Jonathan Harris Sianipar; Novika Candra F; Anjas Handayani; Ali Sunandar (Journal of World Conference (JWC), 2021)
In this study, researchers wanted to discuss the installation of formisting to be installed on the floor plate structure between the girders inside the concrete bridge. In this case the authors want to know the comparison of cost analysis using conventional form form, bondek plate and deckslab. Because the Cost Budget Plan is very much related to the design and selection of materials to be used on girder bridge type I. In construction projects in Indonesia especially on the installation of formware residual material, the use of tools, the location of material procurement is very influential to the cost of construction work therefore it is necessary to be considered and taken into account carefully the selection of efficient formery so that the costs that will be incurred are not overbudget. In the research process this final task requires the foundations of the theory that support the problems that are reviewed. Through the study of literature is expected to be able to increase knowledge and study the basic theory used as a reference. At this stage the activity is a review of literature related to similar case studies from journals, literature books, and previous research reports. Cost analysis is reviewed in terms of services / labor namely, labor users for conventional systems and bondek in the same amount, while for deckslab precast less, but requires more precision. Cost analysis reviewed in terms of equipment, that is, for bondek system equipment does not require complicated equipment, unlike conventional ones that use scafolding aids as well as deckslab precast that use heavy equipment such as crawler cranes and hyab cranes. Price analysis in terms of materials namely, materials for conventional and bondek is very easy to obtain for the price depending on the area of the project location, for deckslab precast is required special supplier because the manufacture is directly from fabrication with a higher price when compared to conventional and bondek. Price analysis of each formisting system is, the installation of conventional formisting with a price of /m2 of Rp. 729,371. The total price of installing bondek form form with a price of /m2 is Rp. 367.593. Total installation price of deckslab precast form work with /m2 price of Rp. 803.795. From the results of the analysis, it can be concluded, that bondek form form form method is worth using for the toll bridge project because in terms of simpler methods and in terms of cost more efficient and effective.